2016
DOI: 10.1007/s00421-016-3413-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of capillary and venous blood in the analysis of concentration and function of leucocyte sub-populations

Abstract: Whilst attention must be paid for varying neutrophilic surface antigen expression and further studies are needed to establish appropriate reference ranges, this study supports the use of capillary blood samples in a site-specific manner to enhance sampling capabilities field-based research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Using whole blood has other advantages, such as avoiding nonspecific cell activation which can occur with some blood processing and cell separation techniques (Himmelfarb et al, 1992). Further, as the test used in the present study is compatible with small blood volumes obtained via fingertip samples, which has previously been shown to be reflective of venous sampling (Canetti et al, 2016), this kit provides greater accessibility to functional tests. However, it should be considered that this method is yet to be validated against other measurements of neutrophil function, including, for example, a test that is considered to be a "gold standard measure" (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Using whole blood has other advantages, such as avoiding nonspecific cell activation which can occur with some blood processing and cell separation techniques (Himmelfarb et al, 1992). Further, as the test used in the present study is compatible with small blood volumes obtained via fingertip samples, which has previously been shown to be reflective of venous sampling (Canetti et al, 2016), this kit provides greater accessibility to functional tests. However, it should be considered that this method is yet to be validated against other measurements of neutrophil function, including, for example, a test that is considered to be a "gold standard measure" (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Both blood compartments certainly differ first in their saturation with respiratory gases since capillary blood is arterial-venous mixed blood (Zavorsky et al 2007 ). Hematocrit and hemoglobin concentration have been found to be higher in capillary samples (Daae et al 1988 ), while for the number of leukocytes were found conflicting results (Schalk et al 2007 ; Canetti et al 2016 ). However, it was repeatedly demonstrated that there are functional differences in immune cells between the two compartments, especially in the function of granulocytes and monocytes (Canetti et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Previous studies have investigated the effects of nicotinic acid on altering blood composition in relation to oxygen saturation testing and fibrinolytic activity. 4,16,17 For example, Canetti et al 18 showed no significant differences between the experimental and control samples in the mean percent of parent (Table 1).…”
Section: Cells 10mentioning
confidence: 91%
“…Previous studies have investigated the effects of nicotinic acid on altering blood composition in relation to oxygen saturation testing and fibrinolytic activity . For example, Canetti et al . recently demonstrated a trend in greater production of reactive oxygen species by neutrophils obtained from a capillary sample compared to the gold standard venous blood sample.…”
Section: Median Fluorescence Intensity (Au) For Granulocytes Monocytmentioning
confidence: 99%